Desempenho agronômico de cultivares de Milho Forrageiro em alto e baixo Fósforo no Sul do Pará. - Coelho, Debora Rodrigues (Universidade Federal do Tocantins, 2024)
Silage produced with the whole maize plant (Zea mays L.) has been an increasingly widespread alternative as a roughage feed for ruminants. One of the main precautions in crop management with a view to silage production is related to fertilization. In tropical soils (such as those in southern Pará State) phosphorus is the most limiting nutrient for agricultural production. Given the above, this work aims to know the agronomic performance of forage maize cultivars in high and low phosphorus in the south of the State of Pará. For this, two competition trials of maize cultivars were carried out under contracting phosphorus conditions: high P (100 kg ha-1 P2O5) and low P (50 kg ha-1 P2O5), using simple superphosphate as a source (18% P2O5). The experimental design was a randomized block with fourteen treatments and three replications. The treatments consisted of fourteen cultivars, eleven of which were hybrids: AG1051, AG8088, BM3061, BR2022, BR205, BR206, BRS3046, CR-120, M274, ORION and PR27D28, and the other three were open pollinated populations (PPA): AL BANDEIRANTE, ANHEMBI and CATIVERDE. The variables evaluated were: Ear Insertion Height (AE) and Plant Height (AP), Total Weight per Plant (PPT), Ear Weight with Straw (PESP) and Ear Weight without Straw (PESP). Means were compared by the Scott & Knott group test, at 5% significance, using the SISVAR program. Considering the general performance of cultivars, in all characteristics evaluated in the two trials, the sum of their results points to cultivar BRS3046 as the most promising for silage production. The high P test, as expected, stood out over the low P test. Keywords: Phosphate fertilization, Tropical soils, Zea mays, Silage.